Analysis and experiment on rolling of strips with various thicknesses in lateral direction. (June 2018) - Wang, Xiaogong; Liu, Xianghua; Wang, Sai; Zhi, Ying
Highlights: A new method for rolling strips with different thicknesses in the lateral direction is proposed. Some key parameters of roll design are determined. Metal in the deformation zone is not under tri-axial compressive stress which is common in traditional flat rolling without tension. RPS samples with a thickness ratio of 1:1.3 were obtained through five passes. Abstract: A new method for rolling strips with different thicknesses in the lateral direction, Rolled Profile Strips (RPS), is introduced. The technological process is simulated by FEM with ABAQUS software to test its feasibility. Three crucial pass parameters, α, the obliquity of the curved deformation area, H, the height of the curved deformation area, and Lstr, the length of the straight part were proposed. Influence of these parameters on rolling results is analyzed before the optimal range is determined. The new method includes bending-spreading rolling (BSR) after which the desired changes in thickness and shape are achieved and flattening rolling (FR) in which the workpiece is flattened. The feasibility is further tested with series of experiments and the characteristics of metal forming in BSR are discussed theoretically. RPS samples with a thickness ratio of 1:1.3 were obtained. Graphical abstract: